Are Emergency Services' Emergency Operation Centres COVID-19 Ready? - Alan Mclean (University of New South Wales, 2020)
Emergency operation centres (EOC) that provide triage, dispatch, command and control for ambulance, police or fire services are considered critical state infrastructure. They provide access to and control of life saving services and are required to be fully operation 24/7. Even minor disruptions to their operations of only a few minutes can potentially result in sever adverse outcomes or deaths within the community. As the COVID-19 is caused by a novel virus it raises questions regarding the bio security preparedness of these facilities. In the absence of published research related EOC operations during a pandemic this paper looks at the emerging public health evidence and how this can be translated to EOC operations.